MEMBINGKAI AYAT-AYAT JIHAD PERANG DALAM KERUKUNAN UMAT BERAGAMA - M. Ridwan Hasbi (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2009)
In the al Quran at least there are 164 verses of jihad war that led to the people to get the glory and give spirit to fight and defend of Islam presence before the non-Muslims. This paper will need to frame verses in the context of inter-religious harmony in which Muslims live in close proximity to each other in many aspects. Frame basis and the principle is the interpretation, the spirit of life that is safe and peaceful and the attitude of Muslims in view of contemporary reality